-5-6(x-4)=11+2x

Simple and best practice solution for -5-6(x-4)=11+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-6(x-4)=11+2x equation:


Simplifying
-5 + -6(x + -4) = 11 + 2x

Reorder the terms:
-5 + -6(-4 + x) = 11 + 2x
-5 + (-4 * -6 + x * -6) = 11 + 2x
-5 + (24 + -6x) = 11 + 2x

Combine like terms: -5 + 24 = 19
19 + -6x = 11 + 2x

Solving
19 + -6x = 11 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
19 + -6x + -2x = 11 + 2x + -2x

Combine like terms: -6x + -2x = -8x
19 + -8x = 11 + 2x + -2x

Combine like terms: 2x + -2x = 0
19 + -8x = 11 + 0
19 + -8x = 11

Add '-19' to each side of the equation.
19 + -19 + -8x = 11 + -19

Combine like terms: 19 + -19 = 0
0 + -8x = 11 + -19
-8x = 11 + -19

Combine like terms: 11 + -19 = -8
-8x = -8

Divide each side by '-8'.
x = 1

Simplifying
x = 1

See similar equations:

| x+3a=34+ax-7a | | 3x-4y=15fory | | 140=7(4+2n) | | 8=-8m+6m | | x/7.3=-.905 | | -13=r-1-5r | | 4+7a+5a=4 | | K/2=13 | | -6n-2nd=16 | | -5(8-7k)+7(1+5k)=-33 | | -.13p-0.05(3-4p)=0.04(p-2)-.25 | | 38=7x+5(x+6) | | -8(5-3x)+4x=-124 | | 90=-6(k-8) | | -82=-2(5x+6) | | (64x-3x+19)= | | -8(1-8v)=-520 | | 4x+1-8=-19 | | -8(1-8v)=-530 | | 6(c+5)=-36 | | 7m-3m=16 | | 3x+3(2x+11)=132 | | 9=b-2 | | 2.6=9.3/x | | 12=3+4b+5 | | 7/2-2/3= | | 9=xb-2 | | 5n+8(4n-3)=161 | | 137=7(3x+7)+x | | x^4+x^9=6 | | -14.2=-1.5k+3.2 | | x-4=10+8 |

Equations solver categories